MEMBANGUN KARAKTER GENERASI MUDA MELALUI MODEL PEMBELAJARAN BERBASIS KECAKAPAN ABAD 21 - Martini, Eneng (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
The purpose of this paper is to re-look at how to build the character of today's young generation if we see still many behaviors or attitudes of the young generation that are far from expectations, this is associated with 21-century skills-based learning model that is being applied in schools, as for the methods used in this writing is the study of several sources of books, journals and other references that support this writing. from the results of theoretical studies can be concluded that the development of character for the young generation today is not separated from the culture and the three environments that support families, schools and communities. The use of 21st century skills-based learning model used in teaching and learning process as a way to build character must be tailored to the needs and objectives of learning, so that the learning objectives can be achieved well.